Employee engagement and remuneration justice in Lithuania and Poland - Marta Juchnowicz; Boguslavas Gruževskis; Hanna Kinowska (Business: Theory and Practice, 2020)
The aim of the article is the analysis of the relationship between work engagement and evaluation of remuneration justice in the context of the dimensions of organizational justice in Lithuania and Poland. The starting point for the research was the identification the essence of evaluation of remuneration justice from the perspective of management sciences. Conclusions drawn from the analysis of the views on organizational justice allowed to define the key aspects of remuneration justice necessary for a detailed exploration of the studied area. They point to the need for a comprehensive evaluation of remuneration justice, integrating all its aspects, not only the distribution aspect. The strong link between fair remuneration and work engagement draws attention to the conditions for effective remuneration instruments. On the basis of the results of empirical research, the assessment of the fairness of remuneration by Polish and Lithuanian employees was diagnosed. In Lithuania, 9% and in Poland 52% of respondents described their current salary as fair. Correlations between the examined constructs were examined. It is concluded that for both working Lithuanians and working Poles fair compensation means remuneration appropriate to the work performed. The sense of fairness of remuneration coexists with distributional, procedural and interactive justice and with the lack of feeling of being exploited.